Functional response in coccinellid beetles (Coleoptera: Coccinellidae) is modified by prey-density experience. Issue 1 (11th January 2022) - Chaudhary, Desh Deepak; Kumar, Bhupendra; Mishra, Geetanjali; Omkar,
Abstract: In the present study, we assessed functional response curves of two generalist coccinellid beetles (Coleoptera: Coccinellidae), specifically Menochilus sexmaculatus and Propylea dissecta, using fluctuating densities of aphid prey as a stimulus. In what may be the first such study, we investigated how the prey density experienced during the early larval development of these two predatory beetle species shaped the functional response curves of the late instar–larval and adult stages. The predators were switched from their rearing prey-density environments of scarce, optimal, or abundant prey to five testing density environments of extremely scarce, scarce, suboptimal, optimal, or abundant prey. The individuals of M. sexmaculatus that were reared on either scarce- and optimal- or abundant-prey densities exhibited type II functional response curves as both larvae and adults. However, individuals of P. dissecta that were reared on scarce- and abundant-prey densities displayed modified type II functional response curves as larvae and type II functional response curves as adults. In contrast, individuals of P. dissecta reared on the optimal-prey density displayed type II functional response curves as larvae and modified type II functional response curves as adults. The fourth-instar larvae and adult females of M. sexmaculatus and P. dissecta also exhibited highest prey consumption (T/ T h ) and shortest prey-handling time ( T h ) on the scarce-prey rearing density. Thus, under fluctuating-prey conditions, M. sexmaculatus is a better biological control agent of aphids than P. dissecta is.